A Brief Retrospective Method for Identifying Longitudinal Trajectories of Adjustment Following Acute Stress. (June 2015) - Mancini, Anthony D.; Bonanno, George A.; Sinan, Beyza
Research increasingly indicates that prototypical trajectories of resilience, recovery, delayed, and chronic distress characterize reactions to acute adversity. However, trajectory research has been limited by the practical and methodological difficulties of obtaining pre-event and longitudinal data. In two studies, we employed a novel method in which trained interviewers provided a graphical depiction of prototypical stress trajectories to participants and asked them to select the one that best described their experience. In Study 1, self-identified trajectories from 21 high-exposure survivors of the September 11th World Trade Center attacks distinguished variation in posttraumatic stress disorder and depression symptoms at 7 and 18 months, and were consistent with trajectories based on longitudinal outcomes and friend/relative ratings. In Study 2, we examined self-identified trajectories from 115 bereaved spouses at 1.5 to 3 years. Persons who identified a resilient trajectory, compared with recovery and chronic distress trajectories, had fewer interviewer-rated symptoms of grief, depression, and posttraumatic stress disorder were rated as functioning more effectively by friends, reported higher life satisfaction, and had fewer somatic complaints. The present results provide initial evidence for the construct validity of a cross-sectional and less demanding method for identifying acute stress trajectories.